Endovascular Treatment Strategy for Acute Basilar Artery Occlusion with Unexpected Right-Sided Aortic Arch - Mizowaki, Takashi; Fujita, Atsushi; Miura, Shinichi; Nakahara, Masahiro; Tanaka, Hirotomo; Matsumoto, Shinichi; Takaishi, Yoshiyuki; Kondoh, Takeshi (Asian Journal of Neurosurgery, 2022)
A right-sided aortic arch (RAA) is a rare variant of the aortic arch found. We present a case of endovascular treatment (EVT) for acute basilar artery (BA) occlusion with an RAA. A 70-year-old man developed acute ischemic stroke due to BA occlusion. During urgent EVT for BA occlusion with an RAA, which was observed unexpectedly, navigation of the catheter to the target vessel was achieved as a result of an early change in the access route. Flexible treatment strategies are warranted for cases of unexpected anatomical variant in the fight against time for emergent cases, such as acute ischemic stroke.
Keywords: right-sided aortic arch; acute ischemic stroke; endovascular treatment